RESEARCH AND EXPERIMENTAL WORK ON PREPARING FUTURE BACHELORS OF PHYSICAL EDUCATION FOR TEACHING ACTIVITIES IN THE CONDITIONS OF INCLUSIVE EDUCATION - ДЕМУС, Я.; ФАЗАН, В. (Педагогічні науки, 2024)
The article is devoted to the disclosure of the methodology of research and experimental work on the preparation of future bachelors of physical education for pedagogical activity in the conditions of inclusive education. A formative experiment program has been developed. An experiment was conducted to determine students' readiness for the inclusive orientation of the educational process. The effectiveness of the developed didactic exercises for the formation of inclusive competence of future bachelors of physical culture for pedagogical activity in the conditions of inclusive education is proven.